Analisis Indikator Pembangunan Bandar Mampan Berdasarkan Penunjuk Bandar Malaysia (MURNInet) Kajian Kes Majlis Bandaraya Alor Setar (MBAS) - Balkis Andresia Putri, , (2012)
Sustainable development is a concept which is coordinating the development of the third sector, namely the development of economic, social and environment to meet human needs while without compromising the needs of future development. One of the monitoring programs of the sustainable development carried out in Malaysia, namely MURNInet which is an approach to measure and asses the sustainability of a city and its affiliates through the use of the city indicators. This study discusses the factors that affect the city of Alor Setar is still at moderate levels at sustainable levels MURNInet. This study used descriptive qualitative approach, in which data collection techniques through direct interviews with the research subjects directly with program MURNInet and three people of civil society. From the results obtained that the imbalance of the third sector of the social, the economy and the environment development can influence the success of sustainable development. Factors that influence the Alor Setar city remains moderate level, namely: weaknesses in the implementation, public and the private sector awareness, incomplete infrastructure, waste of natural resources of water and the coordination and cooperation that has not been maximal.